2019
DOI: 10.1055/s-0039-1681112
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Metalloproteinase Matrix 9 (MMP9) Gene Polymorphisms Risk Factors for Pelvic Organ Prolapse in the Brazilian Population

Abstract: Objective To evaluate the C-1562T matrix metalloproteinase 9 (MMP9) gene polymorphisms as risk factors related to the occurrence of pelvic organ prolapse (POP) and to identify the clinical variables associated with the occurrence of the disease. Epidemiological studies of risk factors for POP do not explain why nulliparous women with no known risk factors also develop POP. Therefore, genetic factors may be involved. Methods Cohort study with 86 women with symptomatic POP (cases), and 158 women with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
(41 reference statements)
0
3
0
3
Order By: Relevance
“…Pelvic organ prolapse (POP) is a health problem that affects millions of women worldwide and manifests in 50% of women over 50 years of age (Subak et al, 2001). Although POP is not a life threatening disease, it impairs the quality of life (QOL) significantly and negatively affects the psychosocial status of the patient due to discomfort and urinary and/or intestinal dysfunctions (Ghersel et al, 2019). Therefore, the treatment of this disease is important to precede the isolation from the social life especially in middle and advanced ages.…”
Section: Introductionmentioning
confidence: 99%
“…Pelvic organ prolapse (POP) is a health problem that affects millions of women worldwide and manifests in 50% of women over 50 years of age (Subak et al, 2001). Although POP is not a life threatening disease, it impairs the quality of life (QOL) significantly and negatively affects the psychosocial status of the patient due to discomfort and urinary and/or intestinal dysfunctions (Ghersel et al, 2019). Therefore, the treatment of this disease is important to precede the isolation from the social life especially in middle and advanced ages.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, its expression was previously examined in women with POP ( Zhu et al., 2020 ). While some studies reported an increase in MMP9 expression in the vaginal tissue of women with POP ( Alarab et al., 2014 ; Dviri et al., 2011 ; Wu et al., 2012 ), others suggested no such increased activity ( Ghersel et al., 2019 ). A significant increase in vaginal MMP9 expression was evident in rodents following vaginal delivery, vaginal distention injury ( Rahn et al., 2008 ), and in the POP transgenic mice model, which do not express the ECM protein fibulin ( Fbln5 −/− mice) ( Chin et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Затем лапароскопической (лапаротомной) бригадой проксимальная часть полоски меша без натяжения сшивается к промонториуму, тем самым обеспечивается надежная фиксация обоих органов (вагино-и ректопексия). Второй бригадой также выполнена по показаниям кольполеваторопластика (7 пациентам), кольполеваторорафия (4), передняя кольпорафия ( 6), вагинальная пластика (5), циркулярная резекция мукозы ПК по Лонго (9), сфинктеропластика (5) и геморроидэктомия (8).…”
Section: результаты и обсуждениеunclassified
“…При этом следует отметить, что начальные формы ПТО проявляются в репродуктивном возрасте: у 19% пациентов до 30 лет, у 65% пациентов -между 30 и 45 годами, и лишь у 17% -после 50 лет, и по мере прогрессирования заболевания появляются и усугубляются функциональные нарушения [2]. В частности, в России данная проблема охватывает до 30% женщин, в Бразилии -27%, в Дании -до 43%, в США -до 23,7%, в Китае -до 40%, в Эфиопии -21% [2][3][4][5][6][7][8]. По прогнозам Lindsay M.K., частота ПТО в США с 2010 по 2030 г. возрастет на 35% и к 2030 г. достигнет среди женщин после 65 лет более 4 миллионов.…”
Section: Introductionunclassified